Influence of Sex on Cognition and Peripheral Neurovascular Function in Diabetic Mice - Fan, Baoyan; Liu, Xian Shuang; Szalad, Alexandra; Wang, Lei; Zhang, Ruilan; Chopp, Michael; Zhang, Zheng Gang (Frontiers in Neuroscience, 2018)
Cognition impairment and peripheral neuropathy (DPN) are two major complications of diabetes. The aim of the present study is to investigate the effect of sex differences on cognition and DPN in diabetic mice. Male and female BKS.Cg-m+/+Leprdb/J (db/db) and db/m mice were used. At ages of 20 and 30 weeks, all animals were subjected to learning, memory and neurological function tests. Regional blood flow in footpad and sciatic nerves were measured using laser Doppler flowmetry. Our data showed that male db/db mice aged 20 weeks and 30 weeks spent significantly more time to locate the hidden platform in the correct quadrant and spent significantly less time exploring the cage with a new stranger mouse compared to aged-matched female db/db mice. Electrophysiological recordings showed that male db mice aged 30 weeks had significantly reduced motor and sensory nerve conduction velocity compared with females. Hot plate and tactile allodynia tests revealed that males exhibited significantly higher thermal and mechanical latency than females. Male db mice aged 30 weeks displayed significantly reduced blood perfusion in sciatic nerve and footpad tissues compared with females. In addition, compared with male and female non-diabetic db/m mice, db/db mice exhibited increased time spent on locating the hidden platform, decreased time spent on exploring the novel odor bead and an unfamiliar mouse, as well as showed significantly lower levels of blood flow, lower velocity of MCV and SCV, higher thermal and mechanical latencies. Blood glucose levels and body weight were not significantly different between male and female diabetic animals (age 30 weeks), but male db mice showed a higher serum total cholesterol content. Together, our data suggest that males develop a greater extent of diabetes-induced cognition deficits and peripheral neurovascular dysfunction than females.